Different meaning of the mean heart dose between 3D-CRT and IMRT for breast cancer radiotherapy - Prunaretty, Jessica; Bourgier, Celine; Gourgou, Sophie; Lemanski, Claire; Azria, David; Fenoglietto, Pascal (Frontiers in Oncology, 2023)
Background: Previous studies in 2D and in 3D conformal radiotherapy concludes that the maximal heart distance and the mean heart dose (MHD) are considered predictive of late cardiac toxicities. As the use of inverse-planned intensity modulated radiation therapy (IMRT) is increasing worldwide, we hypothesized that this 3D MHD might not be representative of heart exposure after IMRT for breast cancer (BC). Methods: Patients with left-sided BC and unfavorable cardiac anatomy received IMRT. Their treatment plan was compared to a virtual treatment plan for 3D conformal radiotherapy with similar target volume coverage (study A). Then, a second 3D conformal treatment plan was generated to achieve equivalent individual MHD obtained by IMRT. Then the heart and left anterior descending (LAD) coronary artery exposures were analyzed (study B). Last, the relationship between MHD and the heart volume or LAD coronary artery volume receiving at least 30Gy, 40Gy and 45Gy in function of each additional 1Gy to the MHD was assessed (study C). Results: A significant decrease of heart and LAD coronary artery exposure to high dose was observed with the IMRT compared with the 3D conformal radiotherapy plans that both ensured adequate target coverage (study A). The results of study B and C showed that 3D MHD was not representative of similar heart substructure exposure with IMRT, especially in the case of high dose exposure. Conclusions: The mean heart dose is not a representative dosimetric parameter to assess heart exposure following IMRT. Equivalent MHD values following IMRT and 3DRT BC treatment do not represent the same dose distribution leading to extreme caution when using this parameter for IMRT plan validation.